Algumas an?lises de solu??es cross-layer para redes TCP/IP sem fio - Mendes, Lucas Dias Palh?o (2009)
TCP wireless networks have its throughput reduced due to channel errors. One of the proposed solutions in the literature for this reduction is Cross-Layer Design. In this work, several Cross-Layer proposals are gathered, categorized and summarized. In order to test the impact of the use of some Cross-Layer proposals, some TCP throughput prediction models were studied. One of the models is corrected and its validity is compared to other TCP model in this work. The comparison of the models shows which of them is capable of predicting the TCP throughput with higher precision when compared to simulated results. Once the best model is known, it is used to prove that there is throughput gain when a chosen Cross-Layer proposal is used. Finally, the impact of the use of another Cross-Layer proposal is analyzed through the creation of a model which is specific to predict the throughput in the considered IEEE 802.11 network and also through the implementation of a Monte Carlo simulator. The analysis of this proposal shows that there is not only a throughput gain, but also the TCP timeouts probability is reduced.